Avaliação da influência da precocidade da antibioticoprofilaxia no risco de infecção em fraturas expostas - Marchiori, João Guilherme Tavares (2022)
Introduction: Open fractures are traumatic injuries capable of fracturing a bone, exposing it to the external environment, with consequent colonization by microorganisms. Open fractures are associated with soft tissue injuries, the severity of which is directly related to the risk of complications, such as nonunion and infection. The goals of treatment are prevention of infection, bone healing, and restoration of function in the affected limb. These goals are most consistently achieved through adequate fracture fixation, meticulous debridement of devitalized tissue and gross contamination, administration of antibiotics, and skin coverage as soon as local conditions permit. One of the variables whose importance has been debated is the time between the occurrence of the fracture and the start of intravenous antibiotic prophylaxis, and represents the central scope of this work. Objectives: To investigate the relationship between time interval to first antibiotic and risk of deep infection, as well as to evaluate epidemiological and microbiological aspects related to open fractures. Finally, to elaborate a systematic review encompassing the topic of the association of timing to first antibiotic and subsequente infection. Methods: the research involves the sequential elaboration of three articles, the first being a study on several epidemiological variables related to fractures, both open and closboth open and closed fractures, treated between February 2019 and March 2020, in a regional hospital of reference in trauma. The second article evaluated associations between several epidemiological variables, especially the evaluation of early antibiotic prophylaxis and the risk of infection in open fractures. The third article consisted of a systematic review that investigated the available evidence regarding the association between early initiation of antibiotic prophylaxis and the risk of infection in open fractures, using the PRISMA algorithm (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and a risk of bias assessment tool (ROBINS-I - Risk of Bias in Non-randomized Studies of Interventions). Results: 416 fractures in 368 patients were included, of which 123 suffered open fractures (139 exposed fractures) and 245 suffered closed fractures (277 fractures). Among women, 83% of fractures were closed, against 57% in men (p<0.0001). As for marital status, 71% were single in the open fracture group, against 50% in the closed fracture group (p=0.0002). Mean age was higher among victims of closed fractures (48.6 years) than among those with open fractures (36.8 years, p<0.0001). Among open fractures, there was a predominance of type IIIA (45%) and, in the closed group, of the AO classification 43 (7.15%). After multiple logistic regression including the variables sex, age, marital status, motorcycle accident, smoking, alcoholism, hypertension and diabetes mellitus, it was observed that only motorcycle accident OR=5.08 (95%CI 2.25-11.50, p. <0.0001) maintained statistical significance as a risk factor for open fractures in relation to closed ones. Of the 123 patients with open fractures, 115 completed the follow-up, with an overall incidence of infection of 18.3%. Of the open fractures of the lower limbs, 23% became infected, against 4% of the fractures of the upper limbs (p=0.04216). Specifically regarding tibial fractures, these accounted for an infection rate of 28%, against 8% for fractures at other anatomical sites (p= 0.010223). The intervals until the start of antibiotic prophylaxis and until the first surgical debridement were not associated with the risk of infection in the bivariate tests (p=0.51 and p=0.19, respectively). The logistic regression model did not obtain statistical significance (p=0.1595), as well as the variable time until the first ATB (p=0.098). The systematic review included 14 studies, of which 6 were considered at serious risk of bias, 7 at critical risk, and 1 at moderate risk. Three studies demonstrated a positive correlation between the interval until the first ATB and the risk of infection, and 11 studies were negative. Regarding the class of antimicrobials used during hospitalization, we found that there was no difference in the risk of infection when comparing the use of a firstgeneration cephalosporin with the expanded coverage therapy for GRAM-negatives. Microbiological studies were obtained for 12 of the 21 infected patients, 21 bacterial strains being isolated, 4 strains of S. aureus, 3 of P.aeruginosa, 3 of E. cloacae and 3 of E.coli. Monomicrobial infections were observed in 66.67% (n = 8) of the patients, of which 5 were infected by a strain resistant to antibiotic prophylaxis. Four strains were classified as MDR, 2 of them being S. aureus. Conclusions: there was no associaation between time to first antibiotic and risk of infection, although this variable approached statistical significance, possibly reflecting a beta-type error, inherent to the sample size limited. The systematic review identified a general low methodological quality of the studies, as well as non-uniform results regarding the association between early antibiotic prophylaxis and reduced risk of infection. Microbiological analyzes show a higher incidence of S. aureus, and that prophylactic antibiotic coverage was innapropriate for 33.3% of the isolated strains.